BUSINESS ANALYSIS OF CERTIFIED COCOA (THEOBROMA CACAO) SEED NURSERIES IN NORTH SUMATRA PROVINCE (CERTIFIED COCOA (THEOBROMA CACAO) SEED BUSINESS ANALYSIS IN NORTH SUMATRA PROVINCE) - Eva Sriana; Retna Astuti Kuswardani; Erwin Nyak Akoeb (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims 1) to find out and analyze how to determine the criteria for certified seeds and 2) to find outand analyze the difference in income levels of certified cocoa seed nursery farms in North Sumatra Province. This research was conducted at seed breeders located in Deli Serdang Regency and Pematang Siantar City. This area was chosen because in these two areas there are certified cocoa seed breeders in the province of North Sumatra. The number of respondents is 5 certified seed breeders who have met several predetermined criteria. The research method used in this study was a survey method, data collection was carried out onJanuary to March 2023.The objectives of this research are answered quantitatively by using the analysis of Total Revenue, Nett Revenue, R/C Ratio and B/C Ratio. The results of the study showed that the cocoa nursery farming carried out provided benefits to all cocoa seed breeders. In the feasibility analysis it is known that the cocoa nursery farming business shows that the cocoa nursery business has received an appropriate assessment of PT. Sahabat Sejati, CV. Prince Agung, CV. Putera perkasa and CV. Dharma Nusantara but the nursery business carried out by CV. Wana Bhakti received an unworthy rating.